2011
DOI: 10.1038/srep00164
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of microfibrillar-associated protein 4 in human cutaneous homeostasis and in its photoprotection

Abstract: UVB-induced cutaneous photodamage/photoaging is characterized by qualitative and quantitative deterioration in dermal extracellular matrix (ECM) components such as collagen and elastic fibers. Disappearance of microfibrillar-associated protein 4 (MFAP-4), a possible limiting factor for cutaneous elasticity, was documented in photoaged dermis, but its function is poorly understood. To characterize its possible contribution to photoprotection, MFAP-4 expression was either augmented or inhibited in a human skin x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 58 publications
6
55
0
Order By: Relevance
“…Thus, molecular interactions between tropoelastin and MFAP4 might positively affect the alignment and maturation of tropoelastin. Because we confirmed previously suggested interactions between MFAP4 and fibrillin-1 (26), it is also possible that MFAP4 together with fibrillin-1 cooperatively promote coacervation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, molecular interactions between tropoelastin and MFAP4 might positively affect the alignment and maturation of tropoelastin. Because we confirmed previously suggested interactions between MFAP4 and fibrillin-1 (26), it is also possible that MFAP4 together with fibrillin-1 cooperatively promote coacervation.…”
Section: Discussionsupporting
confidence: 75%
“…Together, these observations suggest that MFAP4 may contribute to the elastic fiber assembly and/or maintenance. Indeed, MFAP4 has been found to interact with fibrillin-1 and promote elastic fiber formation in in vitro dermal skin fibroblast cultures (26).In this study, we aimed to verify and further characterize the oligomerization pattern of MFAP4 and its molecular interactions with well established elastic fiber components such as tropoelastin, fibrillin-1 and -2, and LOX. We also used site- 3 The abbreviations used are: LOX, lysyl oxidase; COPD, chronic obstructive pulmonary disease; FReD, fibrinogen-related domain; MAGP, microfibrilassociated glycoprotein; Pn, postnatal day n; SPR, surface plasmon resonance; TBST, TBS with 0.05% Tween; TL5A, tachylectin 5A.…”
mentioning
confidence: 99%
“…The molecular functions of these 3 genes have been defined in previous studies. [53][54][55][56][57] However, the role of these genes in tumorigenesis as well as in regulating cell differentiation has not been intensively explored previously-we are the first to identify their potential oncogenic functions in neuroblastoma by participating the cell differentiation process. More remarkably, we found that all the 3 differentiation-regulating targets of miR449a, MFAP4, PKP4 and TSEN15, are significantly correlated with neuroblastoma patient survival, with high mRNA expression levels of these genes in neuroblastoma tumor specimens correlated with poor patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…A role for MFAP4 in the assembly of microfibrils has previously been proposed, 20 but the elastic laminae in the arteries had the appearance of smooth organized lamellar sheets in both Mfap4 +/+ and Mfap4 −/− mice when investigated by transmission electron microscopy ( Figure II mice presented with normal heart rate (HR), blood pressure, circulating cell number, and blood lipid levels (Tables I and II in …”
Section: Characterization Of the Vascular Phenotype In Mfap4-deficienmentioning
confidence: 99%